Differential diagnosis and evaluation in pediatric inflammatory demyelinating disorders. (30th August 2016) - Rostasy, Kevin; Bajer-Kornek, Barbara; Venkateswaran, Sunita; Hemingway, Cheryl; Tardieu, Marc
Abstract : Major advances have been made in the clinical and radiologic characterization of children presenting with the different forms of an acquired inflammatory demyelinating syndrome (ADS) such as acute disseminating encephalomyelitis, neuromyelitis optica spectrum disorders, and clinically isolated syndromes. Nevertheless, a proportion of cases that present with similar symptoms are due to a broad spectrum of other inflammatory disorders affecting the white matter, primary CNS tumors, or neurometabolic diseases. The clinician therefore has to be aware of the different forms of ADS, the risk factors for a chronic-relapsing course, and features that indicate an alternative diagnosis. The goal of this article is therefore to provide an outline of a pathway for evaluating pediatric patients with a presumed inflammatory demyelinating disorder and discussing the spectrum of the more common differential diagnoses.